Pre‐surgical radiographic and clinical features as predictors for temporomandibular joint discectomy prognosis. (14th June 2021) - Minston, William; Benchimol, Daniel; Jacobs, Reinhilde; Lund, Bodil; Krüger Weiner, Carina; Coucke, Wim; Shi, Xie‐Qi
Abstract: Objectives: This study aimed to identify potential clinical and radiological predictors associated with the outcome of discectomies. Methods: In this retrospective observational study, the material comprised preoperative CBCT images and medical records of 62 patients with disc derangement disorders, who had undergone discectomy because of disc displacement with reduction (DDwR), disc displacement without reduction (DDwoR), systemic arthritis (SA), or joint hypermobility. Clinical and radiographic variables were analysed in relation to success rate determined by subjective, objective and combined outcomes. Results: The success odds ratio was 11 times higher in patients with painful DDwR versus that of SA ( p  = 0.03), and even 25.9 times higher when considering solely objective outcome ( p  = 0.03). In the absence of subchondral pseudocyst, there were 5.2 times higher odds to have a successful subjective outcome ( p  = 0.04). Extensive bone apposition on the temporal joint component indicated a 9.3 times higher likelihood of a failed objective outcome ( p  = 0.04). Conclusions: There is a significant higher risk for combined outcome failure for the diagnosis SA involving the TMJ compared with DDwR. Predictors of importance based on CBCT findings related to the objective outcome failure were extensive bone apposition on the temporal joint component and condylar subchondral pseudocysts for the subjective outcome failure.